PETA PEMBAHARUAN PEMIKIRAN ISLAM DI INDIA - Amin, Saidul (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2018)
Indiaisanimportantlandinthehistory ofreformationofreligious thought.There are manyMoslemscholarswere borninthe “India subcontinent”, for example,Syah Waliullah,AhmadKhan,Amir Ali,Iqbal,Ali Jinnah,Kalam Azadandothers.Every oneofthemactually hasasameobjective,torestorethe glory ofIslaminIndia,butuseddifferentapproaches.Theseconditionsspawned manyIslamic Movements,suchasliberalist,orthodox,reformist,andnationalist. Thisarticlewouldliketohighlighttherootofthehistory ofIslamicReform Movement inIndia.